Lepus (Lepus) othus Merriam 1900 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lepus (Lepus) othus Merriam 1900 Lepus (Lepus) othus Merriam 1900, Proc. Wash. Acad. Sci., 2: 28. Type Locality: "St. Michaels, [Norton Sound], Alaska." [USA]. Vernacular Names: Alaskan Hare. Subspecies:: Subspecies Lepus (Lepus) othus subsp. othus Merriam 1900 Distribution: W and SW Alaska (USA); formerly perhaps northwestward to Pt. Barrow; as here interpreted, also E Chukotsk (Russia); if this is verified, tschuktschorum Nordquist, 1883 has priority. Conservation: IUCN – Lower Risk (lc). Discussion: Subgenus Lepus (Averianov, 1998). Formerly included in arcticus or timidus (see comments therein). Regarded as distinct by Hall (1981) and by Flux and Angermann (1990), who, however, followed A. J. Baker et al. (1983) in allying populations from Eastern Siberia (Chukotka) ( tschuktschorum Nordquist, 1883) with Alaskan populations; but see also Pavlinov and Rossolimo (1987). Reviewed by Anderson (1974) who found that othus was closer morphologically to townsendii than to other northern hares. More work is required to determine whether Eastern Siberian populations are linked to L. othus or to L. timidus . If the former relationship is supported, then tschuktschorum Nordquist, 1883 has priority over othus Merriam, 1900. Reviewed by Best and Henry (1994 b , Mammalian Species, 458). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 202, DOI: 10.5281/zenodo.7316519